2016
DOI: 10.5812/ijp.2968
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation oF Epicardial Fat and Carotid Intima-Media Thickness in Obese Children

Abstract: Background:Epicardial fat has a role in cardiovascular diseases.Objectives:To assess epicardial fat and its relation with carotid intima-media thickness (IMT) in obese adolescents with metabolic syndrome (MetS).Patients and Methods:The study included 60 obese adolescents and 25 control subjects. According to the presence or absence of MetS, obese subjects were divided into two subgroups. We measured weight, height, calculated Body Mass Index, waist circumference, hip circumference, systolic blood pressure, dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…With increasing EAT-thickness proinfl ammatory cytokines such as TNF-α, IL-6, IL-8, angiotensin-II, plasma activator inhibitor and free fat acids increase and secretion of cardioprotective cytokines like adiponectin declines (8). A strong correlation between EAT and cIMT has been shown (37,38). The EAT thickness was found to be 0-13.6 mm in the normal population in autopsy series (39).…”
Section: Discussionmentioning
confidence: 99%
“…With increasing EAT-thickness proinfl ammatory cytokines such as TNF-α, IL-6, IL-8, angiotensin-II, plasma activator inhibitor and free fat acids increase and secretion of cardioprotective cytokines like adiponectin declines (8). A strong correlation between EAT and cIMT has been shown (37,38). The EAT thickness was found to be 0-13.6 mm in the normal population in autopsy series (39).…”
Section: Discussionmentioning
confidence: 99%
“…High carotid intima-media thickness measurement in children with metabolic syndrome was shown in studies. 3,30 Elshorbagy et al 31 identified a significant increase in carotid intima-media thickness in metabolic syndrome patients as compared to the non-metabolic syndrome obese and control groups. Hirata et al 32 demonstrated in a study, which included 1727 subjects, that an elevated number of metabolic syndrome components, with or without central obesity, was associated with higher intima-media thickness and, hypertension had the strongest association with higher intima-media thickness.…”
Section: Found Lowermentioning
confidence: 99%
“…Kim et al [37] reported independent associations between epicardial fat and pulse wave velocity in 65 obese Korean adolescents (15–17 years of age). Elshorbagy et al [38] reported that epicardial fat was independently associated with cIMT in subjects with obesity and metabolic syndrome in 60 obese children and adolescents (8–16 years of age) from Saudi Arabia. Similarly, Cabrera-Rego et al [39] and Akyol et al [40] described that epicardial fat was independently associated with cIMT in 66 obese children (9–16 years of age) from Cuba and 138 obese children (9–18 years of age) from Turkey, respectively.…”
Section: Studies In Adolescentsmentioning
confidence: 99%